Secondary Use of Electronic Health Data - Cascini, Fidelia (Springer Nature, 2025)
This open access book provides an in-depth overview of the characteristics, significance, backgrounds and limits of the most relevant electronic health data categories used at a global level for secondary purposes. These include healthcare system improvement, patient safety and quality of care, health policymaking, surveillance of diseases, personalized medicine, research and innovation such as artificial intelligence training for clinical practice. A detailed and thorough representation of published evidence, practical experiences and concrete examples is offered to the reader who has the opportunity to explore the main areas of utilization of electronic health records, biobanking data, genetic and ‘omic’ data, real-world data and many other health data from different sources. The challenges and advantages of health data reuse are explained from a public health perspective that addresses risks, benefits and impacts for different stakeholders such as health data holders (e.g., healthcare providers, pharmaceutical and medical device companies), health authorities and data permit issuers (e.g., health data access bodies), and health data users (e.g., healthcare professionals, researchers, business partners in the healthcare system such as insurers, commercial providers of digital solutions). Given the increasing expansion of health data used for secondary purposes, Secondary Use of Electronic Health Data: Public Health Perspectives, Use Cases and Challenges serves as a go-to resource to facilitate the implementation of health data reuse ecosystems. In this regard, it also highlights emerging opportunities such as the European Health Data Space which is extensively explained.